The Influence of Financing, Financing Risk and Liquidity Risk on the Profitability of Private Islamic Commercial Banks (BUS) in Indonesia - Ningsih, Wiwik Fitria; Handayani, Yuniorita Indah (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
This research aims to determine the effect of mudharabah, musyarakah, murabahah financing, financing risk and liquidity risk on profitability in Private Sharia Commercial Banks in 2019-2023. The study used is quantitative explanatory method. The data used are derived from annual financial reports of Private Sharia Commercial Banks. The population in this research is Private Sharia Commercial Banks listed on the Financial Services Authority (OJK). The sampling technique used is the purposive sampling and obtained 5 banks. The data analysis used are classical assumption testing, multiple linear regression, coefficient of determination (R¬2) and hypothesis testing. The results show that mudharabah financing, murabahah financing, financing risk, and liquidity risk partially have no effect on profitability while partially musyarakah financing has a significant effect on profitability. This result indicate that bank need to develop musyarakah financing, increase operational efficiency and develope effective risk managemen system. Meanwhile sharia banks need to improve management capabilities ini managing mudharabah and murabahah financing and develop new product that are more profitable. Sharia banks have to maintain financing risk (NPF) so that it do not cause potential losses in the future, Sharia banks also need to improve managemen capabilities in managing liquidy risk